APKASS Consensus Statement on Chronic Syndesmosis Injury, Part 2: Indications for Surgical Treatment, Arthroscopic or Open Debridement, and Reconstruction Techniques of Suture Button and Screw Fixation - Hiroaki Kurokawa; Hongyun Li; Chayanin Angthong; Yasuhito Tanaka; Yujie Song; Zhongmin Shi; Samuel Ka-Kin Ling; Patrick Shu‐Hang Yung; Seung Hwan Han; Yinghui Hua; Chen Jiao; Jianchao Gui; et al. (Orthopaedic Journal of Sports Medicine, 2021)
BACKGROUND: The indications for surgical treatment of chronic syndesmosis injury are challenging for many orthopaedic clinicians, as there is no international consensus on the optimal management of these injuries. PURPOSE: An international group of experts representing the field of sports injuries in the foot and ankle area was invited to collaboratively advance toward consensus opinions based on the best available evidence regarding chronic syndesmosis injury. All were members of the Asia-Pacific Knee, Arthroscopy and Sports Medicine Society (APKASS). STUDY DESIGN: Consensus statement. METHODS: From November to December 2020, a total of 111 international experts on sports medicine or ankle surgery participated in a 2-stage Delphi process that included an anonymous online survey and an online meeting. A total of 13 items with 38 statements were drafted by 13 core authors. Of these, 9 items with 17 clinical questions and statements were related to indications for surgical treatment, arthroscopic versus open debridement, and suture button versus screw fixation reconstruction techniques and are presented here. Each statement was individually presented and discussed, followed by a general vote. The strength of consensus was characterized as follows: consensus, 51% to 74%; strong consensus, 75% to 99%; and unanimous, 100%. RESULTS: Of the 17 questions and statements, 4 achieved unanimous support, 11 reached strong consensus, and 2 reached consensus. CONCLUSION: This APKASS consensus statement, developed by international experts in the field, will assist surgeons and physical therapists with surgical indications and techniques for chronic syndesmosis injury.
Keywords: Foot and Ankle Surgery; Shoulder Injury and Treatment; Knee injuries and reconstruction techniques